Internal Mobility Influence on Qualitative Assurance Outcomes as Enhancement of Employee Skills and Competencies - Adebanji Adejuwon William Ayeni; Joseph Sekhampu; Enoima Abraham; Temidayo Raphael Abimbola (Binus Business Review, 2026)
The research examined the correlation between internal mobility and quality assurance outcomes in Nigerian firms. It analyzed survey data from 305 employees in the Fast-Moving Consumer Goods (FMCG), oil and gas, engineering services, construction, and healthcare sectors to determine if structured internal mobility procedures enhanced quality assurance. Data were gathered via a standardized questionnaire and analyzed using descriptive statistics, ANOVA, and regression to examine patterns and identify statistically significant relationships. The findings demonstrate a positive, significant correlation between internal mobility and quality assurance outcomes, suggesting that employee movement across roles and functions enhances competency utilization, reinforces process consistency, and fosters compliance with organizational performance standards. Furthermore, internal mobility serves as a strategy for maintaining quality across corporate processes by systematically enabling people to apply their talents and expertise in diverse contexts. The research can experimentally illustrate the path of internal mobility as a quality-relevant organizational behavior by expanding the scope of human resource development and quality management research beyond its conventional emphasis on training efficacy. Moreover, by presenting evidence from an underrepresented emerging market environment, these findings enhance theoretical comprehension of how talent migration may bolster resilient organizational quality systems. The research highlights the strategic importance of internal mobility as a substitute for external recruitment, providing organizations with a cost-efficient method to uphold performance standards, improve workforce adaptability, and ensure quality assurance in dynamic and competitive operational settings.